Characterization of Chitosan-Bentonite and Water Hyacinth Plant as a Potential Adsorbent - Moondra Zubir; Hafni Indriati Nasution; Mutya Fika Safitri; Agustina Mandasari (Universitas Negeri Medan, 2018)
Water hyacinth (Eichhornia crassipes) has a very rapid growth in the waters so it can cause eutrophication. The silica content of 5.56% allows water hyacinth can be utilized as a natural adsorbent. Bentonit has an advantage as an adsorbent because it has an inter-layered structure that can be easily modified with chitosan, resulting in better performance as an eco-friendly adsorbent. This research aims to determine the characterization of chitosan-bentonite and water hyacinth as a adsorbent of Pb(II)removal. Characterization tests were performed using X-ray difraction (XRD) and Fourier Transform Infra Red (FTIR) spectrophotometry. From the results of quantitative XRD analysis can be seen that the adsorbent of chitosan-bentonit and water hyacinth have different adsorbent characteristic, but has the same crystal system that is triclinic crystal system.